The impact of allogeneic-hematopoietic stem cell transplantation on patients' and close relatives' quality of life and relationships. (April 2016) - Poloméni, A.; Lapusan, S.; Bompoint, C.; Rubio, M.T.; Mohty, M.
Abstract: Purpose: Although evidence suggests considerable disruption to families, the impact of allo-Hematopoietic Stem Cell Transplantation (HSCT) on patients' partners and close relatives has not been sufficiently explored. The present mixed-methods study aimed to enlighten allo-HSCT effects on patients' and close relatives' quality of life (QOL) and their relationships. Methods: Patients who received allo-HSCT between 2007 and 2010 (N = 58) and their close relatives (parents, partners and/or adult children) were asked to respond to an anonymous questionnaire including socio-demographic data, Likert-scale of the impact of HSCT on sexual, couple, family, professional and social life, as well as on perceived support. QOL of patients and close relatives was evaluated (by the FACT-BMT and by WHO-QOL-bref) as were the adjustments of the couples (patients/partners by the DAS). In-depth interviews were performed with patients and partners who consented to this proposition. Results: Patients (N = 28) and close relatives (N = 48) reported fatigue, sleep and sexual problems, emotional distress and relationship difficulties. Patients were mainly concerned with « being a burden » to their close relatives. Close relatives' main concerns were changes in marital and family dynamics, disruptions in daily routine tasks and the responsibility for being the main provider of physical and emotional care. These difficulties increased after HSCT – notably when patients have to face the long-term consequences of the procedure. Conclusion: HSCT has a negative impact on patients' partners and other close relatives' QOL. Data on this topic is still scarce and this study might pave the way for future research in this field and notably guide psychosocial interventions. Highlights: We performed a mixed-method exploratory study. We approached patients' and their close relatives' quality of life issues. We explored the impact of allo-HSCT on patients and close relatives' relationships. We firstly explored dyadic adjustment of HSCT patients.